Summer - Whitehouse, Patricia, 1958- (Chicago : Heinemann Library, 2003)
Describes the sights, sounds, tastes, smells, and activities of summer for young readers.
What is summer? -- What is the weather like in summer? -- What do you wear in summer? -- What can you see in summer? -- What can you smell in summer? -- What can you hear in summer? -- What can you taste in summer? -- What special things do you do in summer?
Includes index.
Horn Book
3.1
K-3.
K-3
Keywords: Summer -- Juvenile literature; Summer; Summer